Designing Strategies for Cleft Lip and Palate Care 2017
DOI: 10.5772/67122
|View full text |Cite
|
Sign up to set email alerts
|

Tympanostomy Tube Placement for Otitis Media with Effusion in Children with Cleft Lip and Palate

Abstract: The condition of cleft lip/palate (CLP) in children is psychologically stressful for family members and debilitating for the patients themselves. These children must undergo a series of major invasive surgeries following birth, including cleft lip repair surgery, cleft palate repair surgery, bone grafting surgery, and dental implant surgery. Unfortunately, the clinical significance of otitis media with effusion (OME), a complication associated with CLP, is often overlooked, and very few studies have explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…The clinical significance of OME is often overlooked and very few studies have explored this condition in depth, despite the fact that it is commonly associated with CLP. The author summarizes and updates his previous work with the article partly borrowing from the author's earlier publications [4,[9][10][11][12][13][14][15][16][17][18][19][20][21]. This paper presents a review of the pathogenesis, clinical manifestations, and diagnoses of OME in children with CLP as well as the controversies surrounding treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of OME is often overlooked and very few studies have explored this condition in depth, despite the fact that it is commonly associated with CLP. The author summarizes and updates his previous work with the article partly borrowing from the author's earlier publications [4,[9][10][11][12][13][14][15][16][17][18][19][20][21]. This paper presents a review of the pathogenesis, clinical manifestations, and diagnoses of OME in children with CLP as well as the controversies surrounding treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a randomized control trial showed that only 56% of patients with CLP treated with VTI had improvements in hearing (Zheng et al, 2003). Many studies have also demonstrated spontaneous resolution of OME and eustachian tube dysfunction by 3 to 4 years of age, deeming placement of VTI for hearing improvement unnecessary (Rynnel-Dagöö et al, 1992; Muntz, 1993; Kuo and Shaio, 2017). These results highlight the need for better data on VTI indications and the ability of VTI to successfully curtail hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Consequently, they often require multiple major surgeries throughout childhood; however, even with surgical intervention, they can experience persistent comorbidities and complications, including hearing loss and postoperative fistulae, that have detrimental effects on learning and development, and often necessitate long-term monitoring and revision surgeries. 5,6 In addition, they may have persistent speech and communication deficits that can impact social development and quality of life. 7 Revision rates for cleft lip and/or palate (CLP) repair range from 9.6% to 57.4%, 8,9 contributing to a substantial emotional and financial burden for patients and their families.…”
Section: Introductionmentioning
confidence: 99%